Variable control in the deep cone thickener in the recovery of highly fluid tailings - Ames Ramírez, Carlos (2011)
This article includes tests in a deep cone pilot thickener, considering the process conditions for optimal flocculation with laboratory tests determining the type of flocculant, concentration of solids in the feed and dosage to maximize the treatment ratio (TPD / m2 ). The objective is to determine the adequate flocculation conditions, which allow the maximum clarity of the liquid and maximum densities in the discharge with the minimum dosage that allows selecting the feeding conditions for the operation of the pilot thickener. Once the feeding conditions have been determined, it follows a series of treatment ratios to determine the maximum possible load under optimal flocculation conditions in terms of TPD / m2. During these series, the solids level is kept constant and the density of the underflow is monitored, maintaining the feed-discharge balance. Overflow, discharge and feed samples were taken as frequently as possible to determine any variations in feed characteristics that may affect flocculation and consequently the clarity of overflow and thickening. Typically, changes in particle size distribution, mineral type, and pH have a major impact.